PWE-122 Parallel Tipss for the Management of Shunt Insufficiency in Patients with Complications of Portal Hypertension: A Tertiary Liver Unit 19 Year Experience. (4th June 2013) - Rajoriya, N; Merzhat, H; Mangat, K; Oliff, S; Tripathi, D
Abstract : Introduction: Transjugular Intrahepatic Porto-Systemic Shunts (TIPSS) insufficiency can be addressed with a side placement of another TIPSS beside the original ("parallel" technique) thus improving portosystemic pressure gradient (PPG). There is a paucity of data assessing the efficacy of this technique. The Aim of this study was to assess the efficacy of parallel TIPSS in a large UK tertiary referral centre. Methods: A retrospective study was performed from patient electronic databases. Parallel TIPSS were performed over a 19 year period. Results: 11 patients (8M:3F) were identified (2% of all TIPSS procedures). Mean age at time of parallel TIPSS was 48.6(+/-13.7). Background aetiology of portal hypertension included: 5 ALD, 2 PSC, 2 PBC, 1 liver graft failure, 1 NCPH. Indications for index TIPSS (5 covered stents) were: 4 Oesophageal variceal (OV) haemorrhage, 3 gastric variceal (GV) haemorrhage, 1 stromal variceal haemorrhage and 3 for refractory ascites. At time of 1st TIPSS, documented mean PPG was 16.6(+/-7.71) and post TIPSS 10.8(+/-7.35) mmHg. Median time between index TIPSS and parallel TIPSS insertion was 72 days (IQR 4–1122 days). Prior to parallel stent placement, 7 patients had dilatation of the index TIPSS. At parallel TIPSS, the mean initial PPG was 16.0 (+/-7.40)/post procedure 6 (+/-2.28) mmHg. 63% had covered stent as the parallel TIPSS. One patient had transient encephalopathy, but no other complications were encountered. Nine patients had a resolution in symptoms. One patient had ongoing GV bleeding requiring Thrombin injection and 1 patient had ascites with no flow in parallel TIPSS 4 days post-procedure. Secondary patency was 82% with a median number of interventions of 1.5 (IQR 1–3). Median follow-up was 30 months (range 0.5–120). 92% patients were alive at 1 month with 86% 1 year survival. Two patients were transplanted during follow-up. Conclusion: Parallel TIPSS is a safe and effective method to treat TIPSS insufficiency. The majority of patients not only had a good haemodynamic result, but also resolution of symptoms. Disclosure of Interest: None Declared.